Tensions regarding inclusion meanings from stakeholders’ perspectives: A qualitative study - María-José Solis-Grant; María-José Bretti-López; Cristóbal Sepúlveda-Carrasco; Cristhian Pérez-Villalobos; Tatiana Sepúlveda-Witt; Eduardo Reinoso-González; Juan Francisco Hernández-Quidel (PLoS ONE, 2025)
In literature, a divergence is apparent concerning the definition of educational inclusion. The study aims to describe the relationship between the diversity of actors in the university community and their perception of institutional inclusion in higher education organizations in Chile. We employed a qualitative methodology based on Grounded Theory, conducting focus groups with 16 students, 17 teachers, five non-teaching staff, and eight authorities. We conducted a semi-structured interview with an authority, encompassing all three university campuses in the country. The data analysis revealed five subcategories associated with the topic. What is understood by the concept of inclusion? What do they think about inclusion? Who should be the subjects of inclusion? What changes have been observed in inclusion? Moreover, why is it necessary to define inclusion? The emphasis is on the diverse existing views around the approach to the concept and the need to generate definitions with institutional relevance to advance its development and implementation.